"Desarrollo de una aplicación web para el control de asistencia y calificaciones complementarias de los docentes de la UTEQ, proporcionando seguridad e integridad en transferencia de datos" - Quiñonez Naranjo, Yazmin Estefanía (2013)
A web application for monitoring attendance and complementary skills of teachers UTEQ, providing security and integrity in data transfer was developed, using the RAD methodology proposed by James Martin to apply the following steps: requirements planning, design, construction and implementation in order to identify the problem situation and the opportunity to improve these problems. Subsequently the information requirements were determined using data collection techniques. Then the system design was produced using the information in the previous stages, through the use case diagrams, physical model of the database. Continually coding web page generated by defining its methods and functions, performing tests to the application to detect and correct errors introduced. The web application has been developed using free software tools for implementation such as: • Eclipse IDE • Postgresql • Java • Start UML This application allows you to create open standards for registration of additional qualifications assigning a percentage value for each job to generate, averaging the ratings facilitating the migration of them to the University Academic System Control and obtain concise and quick reports of the jobs generated by each learning unit